THE RELATIONSHIP BETWEEN THE CONCEPT MASTERY OF MECHANIC MEASURING DEVICES WITH MEASURING ABILITY USING MECHANIC MEASURING DEVICES IN THE TENTH GRADE CLASS OF SMKN 1 SANAMAN MANTIKEI 2015/2016 - Surahman; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2015)
The aim of this research is to find out the relationship of concept comprehention of measurement devices with the measuring ability using mechanic measuring devices in the tenth grade of SMKN 1 Sanaman Mantikei 2015/2016. The research type is a non experiment type with correlational approach. The population is all students of tenth grade of SMKN 1 Sanaman Mantikei with random sampling which is tenth grader Automotive B whose number is 31 students. The instruments of concept mastery of mechanic measurement devices (variable x) is using written test. Before using it, the test instrument should be tested for its difficulty level, differentiation level, validity and reliability level and instrument of the ability to measure using measuring devices (variable y) which is performance test. The research results show the relationship between the concept mastery of using measuring devices (x) with the measuring ability using the mechanic measuring devices (y) in the form of regression formula with correlation coefficient 0,619 which means there is a positive relationship and significant between the concept mastery of using measuring devices (x) with the measuring ability using the mechanic measuring devices (y). The percentage or contribution of the concept mastery of measuring devices (x) is 38,27% on the ability to measure using the mechanic measuring devices (y).